Music and Emotion—A Case for North Indian Classical Music - Valla, Jeffrey M.; Alappatt, Jacob A.; Mathur, Avantika; Singh, Nandini C. (Frontiers in Psychology, 2017)
The ragas of North Indian Classical Music (NICM) have been historically known to elicit emotions. Recently Mathur et al. (2015) provided empirical support for these historical assumptions, that distinct ragas elicit distinct emotional responses. In this review, we discuss the findings of Mathur et al. (2015) in the context of the structure of NICM. Using Mathur et al. (2015) as a demonstrative case-in-point, we argue that ragas of NICM can be viewed as uniquely designed stimulus tools for investigating the tonal and rhythmic influences on musical emotion.